2018
DOI: 10.2967/jnumed.117.204636
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diagnostic 131I SPECT/CT in Long-Term Follow-up of Patients with Papillary Thyroid Microcarcinoma

Abstract: Papillary thyroid microcarcinoma (PTMC) usually has a favorable prognosis but can also be aggressive, with neck and distant metastases. We evaluated the diagnostic role of I SPECT/CT in detecting metastases in PTMC patients during long-term follow-up and whether the procedure should be included in the current diagnostic protocol. We retrospectively studied 351 consecutive PTMC patients who had undergone thyroidectomy and radioiodine therapy; 21 were at high risk, 94 at low risk, and 236 at very low risk. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 23 publications
14
34
0
1
Order By: Relevance
“…In particular, the data obtained in the present study demonstrated that SPECT/CT gave more information on LN staging in an elevated percentage of patients, thus resulting in a completion of TNM staging and risk new stratification. SPECT/CT superiority than planar WBS, that is in agreement with previous results obtained by some authors [16,19,[27][28][29][30], is particularly significant when the latter is inconclusive and thyroglobulin levels are undetectable or very low in VL cases with T1aN0M0, and even more with single LN metastasis. Moreover, SPECT/CT performance was even higher than WBS when the nodes are sited in regions where these can be difficult to be discriminated from thyroid remnants or physiologic structures with elevated iodine uptake, such as those adjacent to submandibular glands that can affect the identification of neoplastic nodes; the latter were detected by SPECT/CT but not by WBS in our patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In particular, the data obtained in the present study demonstrated that SPECT/CT gave more information on LN staging in an elevated percentage of patients, thus resulting in a completion of TNM staging and risk new stratification. SPECT/CT superiority than planar WBS, that is in agreement with previous results obtained by some authors [16,19,[27][28][29][30], is particularly significant when the latter is inconclusive and thyroglobulin levels are undetectable or very low in VL cases with T1aN0M0, and even more with single LN metastasis. Moreover, SPECT/CT performance was even higher than WBS when the nodes are sited in regions where these can be difficult to be discriminated from thyroid remnants or physiologic structures with elevated iodine uptake, such as those adjacent to submandibular glands that can affect the identification of neoplastic nodes; the latter were detected by SPECT/CT but not by WBS in our patients.…”
Section: Discussionsupporting
confidence: 91%
“…In the last years, ¹³¹I-SPECT/CT proved a reliable diagnostic tool to accurately identify and characterize neck LN metastases in DTC patients in both pre-ablation phase post-thyroidectomy [24,26,38], and in post-radioiodine therapy phase [21,[28][29][30][31][32][33] substantially reducing the number of occult and unclear radioiodine avid foci at planar WBS; the latter has been considered for many years the reference imaging method in the diagnostic protocol of DTC after thyroidectomy. In addition, SPECT/CT can determine LN status in the neck more accurately than planar WBS [16,19,[26][27][28][29][30], also identifying rarer parapharyngeal metastases [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations